Dynamics in the Transimpedance Matrix and Electrically Evoked Compound Action Potentials in Cochlear Implant Users With a Lateral-Wall Electrode Array - Jutila, Topi; Sinkkonen, Saku T.; Söderqvist, Samuel; Sivonen, Ville (Lippincott, 2026)
Objectives:
In patients with cochlear implants, tools for measuring intracochlear electric environment as well as neural responses to electrical stimulation are widely available. This study aimed to investigate the possible correlation of changes in the responsiveness of the auditory nerve measured by neural response telemetry with changes in the peak and spread of the intracochlear electric field measured by transimpedance matrix (TIM) in patients implanted with straight electrode arrays.
Design:
In this retrospective study, we analyzed a cohort of 144 ears of 113 consecutive patients who were implanted with Slim Straight electrode array (Cochlear Ltd.) between January 2019 and May 2022. Thirty-four ears of 30 patients had both intra- and postoperative data available for TIM and neural response telemetry thresholds (T-NRT). The postoperative measurements for TIM and T-NRT took place on average 101 (median: 42; range: 22 to 709) and 126 (median: 62; range: 23 to 427) days postoperatively, respectively. In addition, clinical electrode impedances were measured intraoperatively at two time points in 123 ears and postoperatively during all programming visits.
Results:
Electrode impedances gradually increased over time after the onset of the cochlear implant use, and this was more pronounced in the basal part of the electrode array (p < 0.001). Postoperative T-NRTs decreased significantly from the intraoperative measurement (p < 0.001). Postoperative T-NRT between different time points increased slightly in the apical section (p = 0.03) but remained stable in the middle and basal sections of the electrode array. Postoperative intracochlear electric field spread narrowed significantly in the middle section (p = 0.001), and electric field peak value increased significantly in the basal section (p = 0.003) compared to intraoperative values. The increased electric field peak value and the decreased T-NRT between intra- and postoperative measures in the basal section of the electrode array had a significant negative correlation (ρ = −0.42, p = 0.02).
Conclusions:
A novel finding of this study was that the increased postoperative peakedness of the intracochlear electric field was correlated with the increased responsiveness of the auditory nerve in the basal section of the electrode array. The narrower and more peaked intracochlear electric field may be due to fibrous tissue formation around the electrode array. Aligned with the onset of electrical stimulation and the general time course of intracochlear fibrous tissue formation after cochlear implant surgery, a long-term increase in electrode impedances was found, which was more pronounced in the basal section of the array.